COMMUNITY PARADIGM TOWARD THE NAPOSO NAULI BULUNG TRADITION AT WEDDINGS: A PARADOX BETWEEN PRESERVING TRADITION AND ECONOMIC CONSTRAINTS - Huda, M. Ikhwanul; Pasaribu , Indri Lestari; Fitri , Anisa (Balai Penelitian dan Pengembangan Agama Jakarta, 2025)
This study explores the tradition of Naposo Nauli Bulung (NNB) in the customary wedding practices of Kampung Hasobe, South Tapanuli, focusing on its social role and economic impact, particularly regarding the financial burden associated with components such as Uang Tunda, Uang Pataruhon, and Uang Golap. Unlike previous studies that primarily emphasize cultural aspects, this research offers an integrated analysis of both the social function and economic pressures embedded within the tradition. Employing a qualitative case study design, data were collected through in-depth interviews and participatory observation involving six informants, consisting of household heads and active NNB members. The findings reveal that NNB significantly contributes to strengthening social cohesion, fostering collective solidarity, and sustainably reproducing local cultural values. However, the tradition also imposes considerable financial strain, especially on lower-middle-income families, potentially leading to social exclusion. These findings are analyzed through the lens of structural functionalism theory, emphasizing the need to balance the preservation of traditional values with the community’s capacity to adapt to evolving socioeconomic conditions. The study highlights the urgency of reforming the implementation structure of NNB to make it more adaptive and inclusive. It recommends fostering intergenerational dialogue, developing transparent cost guidelines, and actively involving the younger generation in cultural preservation efforts as a strategy for social regeneration. Conducted throughout 2024, this research contributes to the discourse on local cultural practices by integrating economic considerations and community-based social development issues.